Entheseal Doppler signals in ultrasound are associated with vasodilator drugs and age in patients with radiographic axial spondyloarthritis - Magnus Hallström; Anna Deminger; Caroline Feldthusen; Erik Hulander; Mats Geijer; Eva Klingberg; Helena Forsblad-d’Elia (Arthritis Research & Therapy)
Abstract Background The ability of modern ultrasound machines to detect signs of enthesitis has increased, yet there is a lack of studies on patients with long-standing radiographic axial spondyloarthritis (r-axSpA). Hence, we aimed to investigate the prevalence and clinical significance of Doppler signals indicative of inflammation in peripheral entheses of patients with long-standing disease. Methods Patients fulfilling the modified New York criteria for ankylosing spondylitis were included in this cohort study. Peripheral entheses were examined clinically and the presence of focal pain was self-reported on a mannequin. Ultrasound examination of 1692 entheses was performed. Doppler signals were graded from 0 to 3 using color Doppler ultrasound and Smooth Microvascular Imaging. Multivariable linear regression was used to explore factors influencing Doppler signals. Results One hundred and forty-one patients were included with, age (mean (SD)) 60 (12) years, symptom duration 34 (12) years, males 57%, and HLA-B27 86%. Overall, 21.3% of patients presented with ≥ 1 active ultrasound enthesitis (Doppler signals combined with hypoechoic tissue). In 4.3% of patients these findings were tender on palpation. Isolated Doppler signals were found in 89.4–97.1% of patients, with the highest mean Doppler grades in the triceps entheses (0.88), and the lowest in the Achilles tendons (0.28). In multivariable linear regression analysis, age (B (95% CI)) (0.01 (0.00; 0.01), p = 0.004), daily NSAIDs (0.15 (0.00; 0.30), p = 0.048), vasodilator drugs 0.16 (0.01; 0.32, p = 0.041), but not AS disease activity score, were associated with total Doppler scores. Conclusion The prevalence of asymptomatic entheseal ultrasound Doppler findings was overall high. The use of vasodilator drugs and higher age increased the Doppler scores. No association between disease activity and Doppler scores was found in patients with long-standing disease.